Features of the Development of Speech in Younger School Age - Kodirovna, Bozorova Muslima (Pindus Journal of Culture, Literature, and ELT, 2022)
The article deals with the development of students' speech at school age. It is also important to note that speech as a product of social development is a process of communication between people through language that can take the form of messages, instructions, questions, commands, the connection between language and speech, and the development of school-age students' speech. opinions on its specific features are stated.